Monitoring of Urban Growth in Brasília - Anjos, Rafael Sanzio Araújo dos; Vilela, Rodrigo de Oliveira; Bolzon, Ana Clara; Oliveira, Jade (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
The urban Federal District (Distrito Federal ”“ DF), like most Brazilian metropolitan spaces has shown similar problems, differentiating in degree and intensity of its spatial processes. One on the most relevant issues happens due to the quick paced and uncontrolled urban growth, a spatial fact that causes environmental, social, economic, institutional, and political damage, and mainly, compromises the territorial planning process.